Turystyka wiejska w Polsce - ocena tendencji rozwoju na podstawie wybranych cech - Bórawski, Piotr; Brodzińska, Katarzyna (Rural Tourism in Poland - Development Tendencies Estimation on the Basis of Chosen Characteristics, 2006)
The main objective of this research is to recognize differentiation of rural tourist development. The survey proved that central Poland has more places for tourists. The paper presents also the changes in number of foreign tourists. The highest number of tourists visit west and east Polish provinces. Most of them are Germans, Russians and Lithuanians. In Poland the most effective are mazowieckie and lodzkie voivodeships because they use all beds in more than 30 per cent.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 110-115